Exploring the mental healthcare needs of Swiss pre-trial detainees: A pilot investigation of an on-site psychiatric day clinic - Gerth, Juliane; Endrass, Jérôme; Weber, Michael; Graf, Marc; Singh, Jay P.; Rossegger, Astrid (Frontiers in Psychiatry, 2022)
Research has established that justice-involved individuals experience significant mental health problems. However, mental healthcare in correctional settings is often not sufficiently accessible to meet the demand. Hence, to improve the availability of mental healthcare services, especially for pre-trial detainees, the first Swiss on-site psychiatric day clinic (PDC) was established in 2019. The present cross-sectional observational study aimed to evaluate the need of psychiatric care in pre-trial detention and the PDC’s potential to improve it. Methods: File record data were collected from the Office of Corrections and Rehabilitation of the Canton of Zurich. Differences in primary psychiatric care consultations and psychiatric hospital admissions between pre-trial detainees and sentenced prisoners were examined. In addition, a total cohort of pre-trial detainees of the first 18 months of PDC operations was examined to identify differences between three treatment groups: (1) pre-trial detainees exclusively treated in the PDC (n = 41), (2) pre-trial detainees exclusively treated in a psychiatric hospital (n = 58), and (3) pre-trial detainees treated in both the PDC as well as a psychiatric hospital (n = 16). Results: In the five years before the PDC opened, pre-trial detainees had significantly more primary psychiatric care consultations and were admitted to psychiatric hospitals on significantly more occasions than were sentenced prisoners. In the first 18 months of the PDC, psychiatric hospital admission rates for pre-trial detainees decreased by 18.5% and pretrial detainees exclusively treated in the PDC differed significantly from other treatment groups concerning mental disorder, gender, and alleged index offense. They were more likely to be diagnosed with adjustment disorders and were less likely to be diagnosed with schizophrenia spectrum disorder. Conclusion: The use of mental health care among pre-trial detainees is significantly more frequent than among sentenced prisoners concerning both primary care and inpatient treatment. Since establishment of the novel on-site PDC admissions to psychiatric hospitals were found to decrease. Data indicates that especially male pre-trial detainees with adjustment disorders benefitted from this innovative path forward in correctional healthcare. Further research is needed to improve the PDC’s service for female pre-trial detainees.